Impact of Electrolyte Concentration on Surface Properties and Electrochemical Performance of Aluminum Anodes in Aluminum‐Ion Batteries - Nattha Chaiyapo; Yujeong Jeong; Sujeera Plueksachard; Pornjira Phuenhinlad; Panya Thanwisai; Jeffrey Nash; Wanwisa Limphirat; Jayaraman Theerthagiri; Myong Yong Choi; Nonglak Meethong (Advanced Materials Interfaces)
Abstract Aluminum metal is a promising material for aluminum‐ion battery (AIB) anodes due to its sustainable cycle life. However, retaining the stability of aluminum anodes remains a challenge, particularly due to complex interfacial reactions with ionic liquid electrolytes. This study examines the behavior of aluminum foil anodes in varying molar ratios of AlCl3:EMIC ionic liquid electrolytes. Study results reveal that the electrolytes cause damage to the native oxide layer of aluminum foils, leading to their transformation into amorphous aluminum oxide. This is confirmed using Al K‐edge X‐ray absorption spectroscopy (XAS) and X‐ray photoelectron spectroscopy (XPS). In contrast, basic electrolytes promote the deposition of an oxidized layer incorporating anions, which increases interfacial resistance with dendrite formation. These findings highlight the critical role of electrolyte composition in determining surface reactions and stability. This work provides novel insights into the interfacial mechanisms governing aluminum anodes and serves as a guideline for designing stable, non‐aqueous AIB systems.